2020
DOI: 10.3390/molecules25194473
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Immobilized Systems for Microbiological Degradation of Endocrine Disrupting Compounds

Abstract: The rising pollution of the environment with endocrine disrupting compounds has increased interest in searching for new, effective bioremediation methods. Particular attention is paid to the search for microorganisms with high degradation potential and the possibility of their use in the degradation of endocrine disrupting compounds. Increasingly, immobilized microorganisms or enzymes are used in biodegradation systems. This review presents the main sources of endocrine disrupting compounds and identifies the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The reduction in immobilized cell numbers can be attributed to a combination of cell death, matrix leakage (if entrapped), diffusion pathway blockage, and waste toxicity. 79 Wojcieszynska et al 80 reported that while this immobilization system offers several advantages, increasing the number of immobilized cell cycles leads to matrix pore blockage, limiting oxygen and nutrient diffusion. These conditions negatively impact the cells within the beads and their degradation efficiency.…”
Section: Degradation Kineticsmentioning
confidence: 99%
“…The reduction in immobilized cell numbers can be attributed to a combination of cell death, matrix leakage (if entrapped), diffusion pathway blockage, and waste toxicity. 79 Wojcieszynska et al 80 reported that while this immobilization system offers several advantages, increasing the number of immobilized cell cycles leads to matrix pore blockage, limiting oxygen and nutrient diffusion. These conditions negatively impact the cells within the beads and their degradation efficiency.…”
Section: Degradation Kineticsmentioning
confidence: 99%
“…The presence of pharmaceuticals, hormones, and pesticides in the environment pose a threat to organisms due their toxic effects on living cells. In aquatic wildlife, increasing concentrations of both, natural and synthetic hormones cause feminization of male fish, mainly by reducing the size of the testes [4,66,74], and such hormones may change the reproductive performance [53] and negatively affect other reproductive characteristics, as well as the health state of the aquatic ecosystem life in general [20,56,61,68].…”
Section: Introductionmentioning
confidence: 99%